The association between road traffic accidents and visual functions: A systematic review and meta-analysis - Gloria T. Tamenti; Tuwani A. Rasengane; Khathutshelo P. Mashige (AOSIS, 2024)
Background: Poor visual functions have been reported to be related to the occurrence of road traffic accidents. Aim: To review the association between visual function and road traffic accidents (RTAs) from published relevant empirical studies. Setting: Worldwide. Methods: A random effects (RE) model meta-analysis was conducted using STATA 18. Statistical tests conducted include meta-summary statistics, RE meta-analysis (forest plot), meta-regression (relationship between mean age and effect sizes), funnel plots, Egger's and Begg's tests for publication bias and small study effects. Results: A total of 17 relevant studies, which were either cross-sectional or observational by design, were included in the meta-analysis. Reported effect sizes were within computed confidence intervals (CI) at 95%. The computed Q test of homogeneity was 61.94. The overall mean effect size of 1.43 (95% CI of 0.985-1.883) was statistically significant at a 5% level (Z = 6.26; p  0.001). The I-squared = 62.17% (p = 0.00) confirmed moderate heterogeneity and the Q-value of 61.94 (p = 0.00) rejected the null hypothesis that the effect size was the same in all the studies. The funnel plot showed that the remaining majority of 13 studies were within the funnel plot on the right-hand side of the line of no effect. Conclusion: These results provide evidence of associations between visual functions and RTAs, and highlight the need for targeted interventions and further research to address the challenges associated with impaired visual functions and road safety. Contributions: The study contributes to the understanding of the implications of visual functions for road safety.